Evaluasi Sistem Informasi Pemantauan Tindak Lanjut Menggunakan Model Hot Fit - Angga Anugrawan; Yan Rahadian (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
This study evaluates the effectiveness of the Follow-Up Monitoring Information System (SIPTL) of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) based on the HOT Fit Model. Evaluation is focused on external SIPTL or from the auditee side. This research is qualitative research with a case study approach, and the object of the research is the Inspectorate of Majene Regency, West Sulawesi. Evaluation is carried out on human aspects (system use and user satisfaction), organization (organizational structure), and technology (system, information, and service quality). In the human aspect of human resources (HR) management, it shows the suitability of the field of experience, knowledge, and competence. In the organizational aspect, controlling access rights is very good in the form of passwords for each admin and SIPTL inputer. In terms of technology, the speed of access between pages and the addition of features in the SIPTL application is very high. Thus, in general, the external SIPTL application at the Majene Regency Inspectorate has been effective based on the HOT Fit Model. The disadvantages of SIPTL at this time are the absence of regular training for users, communication with users that has not been running optimally, the absence of regular password changes, and the absence of regular application updates. Further research is recommended to evaluate the internal SIPTL, namely from the perspective of BPK RI as a user and the addition of research objects as a comparative analysis.